Topology optimization of disk–shaft rotating body under thermomechanical coupling - Yu Wang; Renfu Li; Xiaowei Liu; Kun Wang (Case Studies in Thermal Engineering)
Turbine rotors often operate under harsh conditions, such as high rotational speeds and large temperature gradients, that requires them to withstand complex thermal and centrifugal loads. This demands careful design of their internal and external structural configuration to balance the performance and the cost. Using volume as the optimization objective with compliance and stress as the constraints, this paper presents a thermomechanical coupling topology optimization approach for the design of disk–shaft rotating structure. The influences of factors such as the rotational speed, thermal conditions, and central hole on the optimization results are analyzed. The results show that for a disk–shaft rotating body with a central hole, a “waist-like” structure that is characterized by root fusion of thick webs and large holes resists centrifugal loads well. When thermal loads are considered, the optimized configuration becomes more complex, and a “finger-like” structure with a main stem and multiple branches offers an enhanced load-bearing performance. For a disk–shaft rotating body without the central hole, a “palm-like” structure with thick branches exhibits high load-bearing capacity. Additionally, at high rotational speeds, the disk–shaft rotating body without a central hole experiences a lower overall stress than the disk–shaft rotating body with a central hole of the same radial size. For disk–shaft rotating bodies, although the thermal stress constitutes a relatively small proportion of the total stress, it still significantly affects the optimized configurations.